Bidding Strategies in Discos for Deregulated Electricity Market - S. Padma, S. Arun Kumar, T.J.Deepika, A. K. Sowmya (International Journal of Advanced Science and Technology, 2020)
Deregulation in power industry is restructuring of the rules and economic incentives that government set up to control and drive the electrical power industry. Bidding by participants is one of the major challenges. To overcome this issue, strategic bidding models are being developed based on Market Clearing Price, power market structure, auction rules and bidding protocols. This project proposes to develop a detailed bidding strategy for DisCos based on Market Clearing Price (MCP) and analyze its impact in the market operations. Suppliers (GENCOs) and consumers (DISCOs) participant in the bidding process in order to maximize their and benefits. Each DISCO bids strategically by choosing the bidding coefficients to counter the competitors bidding strategy. Power Exchange market, which is simple yet enables competition, will be considered. This is proposed to be done using MATLAB coding and particle swarm optimization. Linear non-increasing bids are proposed to be formulated for DISCO. The MCP computations by power exchange (PX) are then done to analyze the status of the proposed bid in the power market. This process is repeated for various values of DISCO bids till an optimal point is reached, in terms of cost minimization and profit maximization of the DISCO. The proposed method of this system by using particle swarm optimization.